SPINAL CORD INFARCTION AS A RARE NEUROLOGICAL COMPLICATION OF ANTERIOR STEMI FOLLOWING FIBRINOLYTIC THERAPY: A CASE REPORT - Novia Heriza; Subandi (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Spinal cord infarction (SCI) is a rare cause of acute neurological deficits and an exceedingly uncommon embolic complication of acute myocardial infarction (AMI). The primary mechanism involves cardioembolism originating from a left ventricular (LV) mural thrombus. We report a rare case of SCI presenting as acute paraplegia following fibrinolysis for anterior ST-elevation myocardial infarction (STEMI). Case: A 53-year-old man presented with typical chest pain. Electrocardiography demonstrated anterior STEMI, and fibrinolytic therapy with streptokinase was administered immediately. Six hours later, he developed sudden bilateral lower-limb weakness, sensory loss from the toes to the T10 level, and urinary retention. Neurological examination showed complete paraplegia (motor strength 0/0) with loss of pain and temperature sensation below T10, while vibration and proprioception were preserved, consistent with Anterior Spinal Artery Syndrome (ASAS). Spinal magnetic resonance imaging revealed T1-hypointense and T2-hyperintense lesions in the anterior horn at the T10 level, confirming anterior spinal artery infarction. Discussion: Acute paraplegia after fibrinolysis was strongly suspected to result from an embolic shower caused by destabilization of an LV mural thrombus, leading to occlusion of the radiculomedullary artery and subsequent ASAS. Because neurological recovery is often limited, prompt anticoagulation and early rehabilitation are essential to optimize outcomes. Conclusion: SCI is a rare but serious complication of anterior STEMI associated with LV thrombus formation, which may cause cardiogenic embolism through the artery of Adamkiewicz. Clinicians should maintain a high index of suspicion for spinal cord stroke in post-STEMI patients, particularly after fibrinolytic therapy, to facilitate timely diagnosis and management.